2018
DOI: 10.1002/cbf.3335
|View full text |Cite
|
Sign up to set email alerts
|

Pristimerin targeting NF‐κB pathway inhibits proliferation, migration, and invasion in esophageal squamous cell carcinoma cells

Abstract: Although several approaches including surgery, chemotherapy, and radiotherapy had been applied in the treatment of ESCC, more effective targeted chemotherapies are required to increase the survival rates of patients. This study suggested that inhibiting NF-κB signalling pathway could be an effective approach for the treatment of ESCC. Pristimerin, a potent NF-κB inhibitor, exerted potent anti-ESCC effects both in vitro and in vivo, which may be a promising therapeutic agent for ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Matrix metallopeptidase (MMP) is considered as an important member of the invasive process, which cancer cell secreted to dissolve the components of ECM or basement membrane [31]. It was previously reported that pristimerin down-regulated MMP2 and matrix metallopeptidase 9 (MMP9) to inhibit migration and invasion of esophageal squamous cell carcinoma (ESCC) [32]. Similarly, we found an obviously decreased expression of MMP2 in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Matrix metallopeptidase (MMP) is considered as an important member of the invasive process, which cancer cell secreted to dissolve the components of ECM or basement membrane [31]. It was previously reported that pristimerin down-regulated MMP2 and matrix metallopeptidase 9 (MMP9) to inhibit migration and invasion of esophageal squamous cell carcinoma (ESCC) [32]. Similarly, we found an obviously decreased expression of MMP2 in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Pristimerin, a naturally occurring triterpenoid, targets the NF-κB pathway to inhibit the proliferation, migration and invasion of oesophageal squamous cell carcinoma cells. 15,16 Reactive oxygen species (ROS) have important roles in mediating cell proliferation, migration and angiogenesis through the regulation of many key intracellular signalling pathways including Akt, Stat3, and NF-κB. 17 Nicotinamide adenine dinucleotide phosphate (NADPH) oxidases (NOXs) are an important source of ROS.…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that tumorigenesis is a complex process that involves the interaction of various genes and signaling pathways [26,27]. In ESCC, an increasing number of signaling pathways have been reported to play important roles in the progression of the disease [28][29][30]. Therefore, the analysis of pathways related to neoplasia could provide information regarding tumor development.…”
Section: Discussionmentioning
confidence: 99%